PENGARUH SUHU DAN WAKTU PENYANGRAIAN TERHADAP RENDEMEN DAN MUTU MINYAK KEMIRI - , John Tibo Kana Tiri ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Candle nut oil-making process conducted by boiling or roasting in traditional way provides low quality standard of candle nut oil yielded so it becomes less competitive in the market. A laboratory study on candle nut oil was conducted to investigate the condition of temperature and appropriate time duration of roasting in producing high yield of candlenut oil and to determine the condition of temperature and appropriate time duration of roasting providing high quality of candle nut oil obtained. The studies was arranged factorially in Completely Randomized Design, consisting of two factors: factor I was levels of temperatures of 90, 120, and 150Â°C